FORMULATION AND EVALUATION OF MICROEMULSION GEL FOR TRANSDERMAL DELIVERY OF TRAMADOL - MURUGANANTHAM V; PRABAKARAN M; PASUPATHI C; PEELY LR; POOJA B (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present work was carried out to design microemulsion gel system for transdermal delivery of the drug to minimize the side effects and to reduce the frequency of administration and for prolonging the duration of action. Methods: Tramadol, an opioid analgesic drug, was mixed with various selected polymers such as sodium alginate (SA), acacia, hydroxypropyl methylcellulose (HPMC), and Eudragit in geometric mixing ratios. The drug, polymer, and other excipients were mixed thoroughly by trituration method and different formulations (F1-F8) were prepared the same quantity of all the ingredients excepting the polymers. Results: The different formulations prepared, studied, and showed that the formulation using SA as polymeric carrier had a better effect on the evaluated parameters. The drug-SA formulation exhibited better drug-polymer compatibility, optimal viscosity (2750 cps), zeta potential (−26.1 Mv), and particle size distribution (262.8 d.nm) values. The in vitro release studies also indicated that the drug-SA formulation was of desirable release pattern, thus indicating that SA to be a better choice in formulating a transdermal delivery gel system. Conclusion: Evaluated microemulsion gel formulation F2 of tramadol with polymeric carriers SA was much stable than other carriers used. Thus, it could be concluded that the gel formulation with SA can be taken as an ideal formulation.